2022
DOI: 10.5194/egusphere-egu22-5657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catchment memory explains hydrological drought forecast performance

Abstract: <p>Skillful Drought Early Warning Systems (DEWSs) to predict drought a few months in advance are of utmost importance to reduce the impacts of the drought hazard. Previous studies on meteorological drought forecasts e.g. using the standardized precipitation index (SPI) show that drought can be sufficiently predicted up to 1-3 months ahead. The skill of hydrological drought forecasts e.g. using the standardized runoff index (SRI) and standardized ground index (SGI), on the other hand, is even 2-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…At a regional scale, antecedent values of P/PET from the prior year displayed similar correlations to those for the present year with drought metrics, implying a long‐term effect of below normal precipitation on drought due to lagged propagation of depleted soil storage and groundwater levels (Apurv & Cai, 2020; Apurv et al., 2017). Prior research has shown that for fast‐responding catchments P/PET plays an important role in driving streamflow drought onset, duration and severity, but that for catchments that respond more slowly due to their size, topography, and subsurface properties, catchment memory suppresses the influence of short‐term response to P/PET (Sutanto and Van Lanen, 2021, 2022; Van Lanen et al., 2013; Van Loon & Laaha, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…At a regional scale, antecedent values of P/PET from the prior year displayed similar correlations to those for the present year with drought metrics, implying a long‐term effect of below normal precipitation on drought due to lagged propagation of depleted soil storage and groundwater levels (Apurv & Cai, 2020; Apurv et al., 2017). Prior research has shown that for fast‐responding catchments P/PET plays an important role in driving streamflow drought onset, duration and severity, but that for catchments that respond more slowly due to their size, topography, and subsurface properties, catchment memory suppresses the influence of short‐term response to P/PET (Sutanto and Van Lanen, 2021, 2022; Van Lanen et al., 2013; Van Loon & Laaha, 2015).…”
Section: Discussionmentioning
confidence: 99%